Cabaran Kerja Penyelenggaraan Bangunan Kediaman Bertingkat Selepas Banjir - Suhaimi, Nurul Sahiraini; Sarpin, Norliana; Omar, Roshartini; Kai Chen, Goh; Md. Gharip, Nor Hazlin (Research in Management of Technology and Business, 2023)
Maintenance work is an important activity in a building to ensure that it functions properly. This maintenance work needs to be given more priority when it comes to building maintenance after a natural disaster such as a flood. This is because there is a lot of damage that happened after the flood happened. Therefore, this study was conducted to achieve objectives such as identifying important factors that need to be considered in building maintenance work, identifying challenges in building maintenance work and suggesting improvements for high-rise residential building maintenance work after a flood. This study uses a qualitative method involving an interview with 4 respondents who are the personnel from management of the apartment buildings around Taman Sri Muda, Shah Alam, Selangor. Meanwhile, the method of data analysis is content analysis. The findings of the study found that the factors that need to be considered in the maintenance of high-rise residential buildings after a flood include sufficient funds, standardized work procedures, skilled staff, replacement work of materials and components, understanding related the importance of maintenance work, and the feedback of related parties. Some of the challenges of high-rise residential building maintenance work after the flood are lack of funds for maintenance, arrears in payment of maintenance fees by residents, lack of skilled maintenance workers, lack of training among workers, and lack of spare parts and equipment. While the improvement for the maintenance of high-rise residential buildings after the flood incident is by improving the quality of maintenance, to ensure that maintenance policies and guidelines are followed, to ensure that the building is well maintained, and to improve the complaint system. Therefore, this study was conducted to find out the recommended practices for building management in managing challenging maintenance work, especially for residential buildings involved in flood incident.